Malaria infection and anaemia in HIV-infected children in Mutengene, South west Cameroon: a cross sectional study - Bate, Ayukenchengamba; Kimbi, Helen K.; Lum, Emmaculate; Lehman, Leopold G.; Onyoh, Elias F.; Ndip, Lucy M.; Njabi, Conica M.; Tonga, Calvin; Wempnje, Godlove B.; Ndip, Roland N; Bessong, Pascal O. (BioMed Central, 2016)
Background: Malaria is one of the leading causes of morbidity and mortality in children and HIV infection as well as other factors may worsen the situation. This study was aimed at determining the factors influencing malaria parasite prevalence and density as well as anaemia in HIV-infected children in Mutengene, Cameroon from November, 2012 to April, 2013. Methods: A semi-structured questionnaire was used to record information on socio-demographic factors and use of preventive measures by caregivers of HIV-infected children aged 1–15 years and of both sexes. Venous blood was collected; blood films were prepared and Giemsa-stained for parasite detection and speciation. Haemoglobin concentration was measured and the anaemic status determined. Data was analysed using Epi Info 7 software. Results: A total of 234 children were studied. The overall malaria parasite prevalence was 24.8 % (58) and was significantly higher (31.9 %, P = 0 .004) in females, those who did not implement any preventive measure at all (66.7 %, P = 0.03) and children who used antiretroviral therapy (ART) (28.6 %, P = 0.02) when compared with their respective counterparts. Geometric mean parasite density (GMPD) was significantly higher (3098.4, P = 0.02) in children who presented with fever, had CD4 T cells ≥500 cells/μL (491.3, P = 0.003) and those with moderate anaemia (1658.8, P = 0.03) than their respective counterparts. Although there was no significant difference, GMPD was however higher in males (549.0); those not on ART (635.0) and highest in children <5 years old (633.0) than their respective counterparts. The overall prevalence of anaemia was 49.6 % (116). The value was significantly highest (58.3 %, P = 0.01) in the 11–15 years age group; those with CD4 T cell level 200–499 (72.7 %, P = 0.001) and children with fever (85.7 %, P = 0.01). Conclusion: Implementation of proper and integrated malaria preventive measures as well as frequent monitoring of anaemia on prescription of ART could likely improve the health conditions of HIV-infected children thus avoiding malaria-related morbidity and mortality.
Publication of this article was funded by the Department of Zoology and Animal Physiology, Faculty of Science, University of Buea, Cameroon
Keywords: Malaria parasite prevalence and density; UCTD; HIV-infected children; Anaemia; Cameroon